Behavioral Intention: An Overview And Blibliometric Analysis - Raisa Rahma, Deshinta; Hermawan, Agus (Rifa'Institute, 2023)
The aims of this research is to explore the topic of ‘behavioral intention’. The literature analyzes from 30 articles from Scopus using Publish or Perish during the period 2018-2023, analyze with blibliometric. The outcome of the review indicated 109 authors from co-authorship data and many recent keywords from co-occurrence. This literature review can be used for a guidance to the next researcher regarding behavioral intention and the connection with other keywords that appropriate.